Study of Chlorella vulgaris from Different Growth Phases as Biosensor for Detection of Titanium and Silver Nanoparticles in Water - Thenarasu A.; Chai M.K.; Tan Y.H.; Wong L.S.; Rajamani R.; Djearamane S. (Technoscience Publications, 2025)
The increased use of metallic nanoparticles has led to concern for environmental contamination and disruption in water quality. Therefore, effective screening of metallic nanoparticles is important for detecting metallic nanoparticles in aquatic environments. Biosensors offer several advantages, including high sensitivity to pollutants, short response time, energy efficiency, and low waste generation. In this study, a whole-cell biosensor was developed using microalga Chlorella vulgaris as a recognition element, and its fluorescence response was used as a measuring parameter for detecting the presence of titanium dioxide (TiO2) and silver (Ag) nanoparticles in water. The responses of C. vulgaris at the lag, exponential, and stationary phases to different concentrations of TiO2 and Ag nanoparticles were studied. The results showed that in TiO2 and Ag nanoparticles exposures, the highest fluorescence change (50-150%) was observed at the lag phase, whereas the lowest fluorescence change (40-75%) was observed at the stationary phase. A significant fluorescence change was observed in 15 min. The immobilized C. vulgaris under TiO2 and Ag nanoparticles exposures showed 30-180% higher fluorescence change than the negative control, indicating the potential of C. vulgaris as a biosensor for rapid detection of TiO2 and Ag nanoparticles in water. The mathematical modeling of the responses of C. vulgaris to TiO2 and Ag nanoparticles at 15 min of exposure with high R2 indicated that this biosensor is sensitive to the concentration tested (0.010-10.000 mg.L-1). Taken together, these results reveal that, for the first time, it is possible to detect TiO2 and Ag nanoparticles in water within a very short time using a microalgae-based biosensor. Moreover, no genetic engineering requirement makes this biosensor simple, economical, and free from the restriction on genetically modified microorganisms for environmental applications. ? 2024 Technoscience Publications. All rights reserved.